Rationale for ablation of oligometastatic disease and the role of stereotactic body radiation therapy for hepatic metastases. (January 2014) - Rusthoven, Chad G; Schefter, Tracey E
SUMMARY Management paradigms for metastatic solid tumors are evolving. Once regarded as uniformly incurable, today there is recognition of an intermediate oligometastatic state, where ablation of metastatic foci may improve disease control and prolong survival. In the setting of limited colorectal liver metastases, hepatic resection has resulted in favorable long-term outcomes, but is technically unsuitable for most patients. Stereotactic body radiation therapy represents an effective, noninvasive means of tumor ablation, supported by a large body of prospective evidence specific to hepatic metastases. This review examines the current rationale for ablation of oligometastatic disease, including various objectives beyond indefinite disease-free survival. The role of stereotactic body radiation therapy for ablation of hepatic metastases is then comprehensively reviewed.